PERANCANGAN DAN IMPLEMENTASI METODE KERJA YANG ERGONOMI PADA PT. CAHAYA ANUGRAH SENTOSA MAKASSAR - Yunus, Kartini (JNSTA ADPERTISI JOURNAL, 2023)
Cahaya Anugrah Sentosa Makassar produces peanut egg snacks. In the production process of this egg peanut snack has a fairly high risk because the work process is carried out continuously. This process still uses human power without the use of work aids. Besides that, the process of packing egg nuts snacks isdone on the floor in a sitting position. This is very dangerous for the work force because it has a risk of occupational diseases, fatigue at work, so that workers become uncomfortable at work. The purpose ofthis study is to design ergonomic work methods in the packing section to reduce the risk of occupational diseases and will increase work productivity. The method used in this research is subjectivity analisysis and anthropometric analisis. From the subjectivity analysis it can be seen the level of operator complaints, while antropometric analysis obtained the operator’s body size which can be adjusted to design work aids. From the results of the oprator subjectivity analysis, it can be seen that the comparison of the level of complaints before and after the design of work methods. Prior to the design of the work methods, the average complaint scale has not felt pain and is not tired for along time